Community Assistance in the utilization of Nickel Slag in the Morosi Village - Firdaus; Awaliah, Wd Rizky; Anshari, Erwin; Wahab; Deniyatno; Mili, Marwan Zam (Teras Kampus as a member of PT Palem Edukasi Nusantara, 2024)
Morosi Village located in Konawe Regency is one of the areas in which there is a nickel processing company. The nickel processing produces solid waste, one of which is nickel slag. The amount of nickel slag is accumulating day by day, because each process of refining one ton of nickel product produces 50 times the solid waste, equivalent to 50 tons. So that from the results of quite a lot of waste, research was carried out to use solid waste as a concrete forming material, either as coarse and fine aggregate, or as a cement mixture. Government Regulation No. 101 of 2014 classifies nickel slag as B3 waste hazard category 2 with waste code B403. This means that nickel slag is a waste that has a delayed effect, and has an indirect impact on humans and the environment. Meanwhile, at the end of 2019, the Indonesian National Standard (SNI) concerning the choice of nickel slag material from electric furnaces. This SNI was also prepared by the Ministry of Industry to support the development of nickel slag standards and as a solution for nickel slag management. The existence of SNI is also intended as a reference to optimize the use of nickel slag as aggregate, substitute for natural aggregate and other uses. Some examples of products made from nickel slag include bricks, precast and ready-to-print concrete, road base and field, soil improvers, growing media and fertilizers, mortar and cement slag, composite portland cement, and cement geopolymers. To accommodate the use of nickel slag, assistance is needed to the community, especially in Morosi Village to be able to process with appropriate, effective and efficient technology in accordance with its physical characteristics and chemical characteristics. This will be an alternative to reduce the amount of nickel slag that can pollute the environment, in addition to increasing people's income.